IMPROVEMENT OF THE SMELTING TECHNOLOGY OF STEEL IN ACIDIC AND BASIC ELECTRIC ARC FURNACES IN «SAMARA PLANT TECHNICAL CASTING» WITH THE USE OF DISPERSED MATERIALS - A. V. Chaikin; A. V. Kolkolova; A. I. Guscin; V. A. Chaikin (Литьë и металлургия)
Efficiency of using particulate materials as deoxidazing mixtures for steel diffusive deoxidation in acid and basic furnaces is shown.